A GIS-based analysis of the potential for freight villages in Turkey. (1st January 2013) - Pekin, Ethem; Macharis, Cathy
Over the last decade, significant growth has been realised in the sector of the maritime container traffic in Turkey, but moving freight towards the hinterland by rail is still a major problem. In addition to the liberalisation of the Turkish State Railways and the national development plans towards enhancing transport network, intermodal terminals (freight villages) are also being constructed. Today, private initiatives have started to offer intermodal rail services between seaports and the inland terminals. An initial decision making problem in this setting is about the location of an intermodal terminal. The objective of this paper is to propose a geographic information system (GIS)-based location analysis model to analyse the Turkish intermodal terminal landscape. Taking transport price as the main modal choice variable, the model aims to minimise the total sum of transport prices and visualises the results using GIS maps. The model is used as a policy support tool to highlight intermodal transport potential and to demonstrate a vision on the future development of intermodal transport in Turkey.